HELICOBACTER PYLORI AND ITS INFLUENCE ON CLINICAL AND ENDOSCOPIC MANUFESTATION OF GASTROESOPHAGEAL REFLUX DISEASE IN CHILDREN - M.Sh. Babadzhanova ("Paediatrician" Publishers LLC, 2009)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):119-120)